Expression of Ki-67 nuclear antigen in B and T cell lymphoproliferative disorders. Issue 8 (August 1992) - de Melo, N; Matutes, E; Cordone, I; Morilla, R; Catovksy, D
Abstract : AIMS: To determine whether the proliferation rates of tumour cells may relate to prognosis and reflect disease activity. METHODS: Blood mononuclear cells from 155 patients with B cell (n = 120) or T cell (n = 35) chronic lymphoproliferative disorders were tested with the monoclonal antibody Ki-67 by indirect immunoperoxidase or immunoalkaline phosphatase techniques. B cell diseases included chronic lymphocytic leukaemia (CLL), CLL in prolymphocytic transformation (CLL/PL), prolymphocytic leukaemia (B-PLL) and non-Hodgkin's lymphoma (B-NHL) in leukaemic phase. The T cell diseases comprised large granular lymphocyte (LGL) leukaemia, T-PLL, and T-NHL. RESULTS: These showed significantly higher proportions of Ki-67 positive cells in T cell (11.2%) than in B cell (2.9%) disorders (p < 0.001). The highest values were found in NHL of both B and T cell types, particularly when low grade disease transformed to high grade. The lowest percentages of Ki-67 positive cells were found in CLL (1.4%) and LGL leukaemia (1.7%); intermediate values were seen in B PLL (3.3%) and T PLL (5.8%). CONCLUSIONS: There is a positive correlation between prognosis and proliferation rates in chronic B and T cell lymphoproliferative disorders. Estimation of Ki-67 in circulating leukaemic cells could be used to determine prognosis in low grade malignancies.